Pengaruh Kinerja Keuangan Terhadap Harga Saham Perusahaan Farmasi Periode 2017-2019 - Karimatus Zahro S. Hikmah Jamil (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2020)
The purpose of this study was to determine the effect of financial performance on stock prices in pharmaceutical companies listed on the Sharia Securities List (DES) for 3 years. One way to analyze the value of stock prices is using financial ratio analysis. The ratios used in this research are Current Ratio, Debt to Equity Ratio, Return On Equity, Total Asset Turnover and Price Earning Ratio. The sampling technique used purposive sampling technique which consisted of 5 companies. The data source uses the company's financial statements and stock prices from the official website of the Indonesia Stock Exchange (IDX) or the Indonesia Stock Exchange (IDX). The research approach uses quantitative with descriptive methods. Data analysis used panel data regression analysis with data analysis tools Eviews 9. The results of the simultaneous analysis showed that financial performance had a positive effect on stock prices of pharmaceutical companies. The value of the coefficient of determination in this study is 0.871935 which explains the variation of the dependent variable by 87.19% while 12.81% is explained by other independent variables outside the model.